Radical anions of substituted nitro- and dinitrobenzenes - V. M. Kazakova; N. E. Minina (Тонкие химические технологии)
This article presents the results obtained by means of polarographic investigation and EPR spectra in a series of substituted nitro- and meta-dinitrobenzenes in aprotic solvents. The theoretical data obtained with the use of quantum-chemical MOHcalculations with Mac Lachlan correction and INDO were discussed.